Creativity and Ownership: Protection of Rights in Musical Works in the European Union From Digitisation to Artificial Intelligence: Креативност и власништво: правна заштита музичких дела у Европској унији од дигитализације до вештачке интелигенције (MUZIKOLOGIJA-MUSICOLOGY, 2024)
Even more than intelligence, creativity is considered as a quintessentially human capacity. The same conclusion is fully applicable to the artistic creation in music sector. However, rapid technological development is constantly challenging not only the creative process as such, but also the legal instruments intended to protect the results of intellectual and artistic work. The first part of this article examines the provisions of the new EU Directive 2019/790 dedicated to online content-sharing service providers and fair remuneration of authors/performers, while its second part maps the main challenges the development of artificial intelligence imposes to the protection of rights in musical works.